2002
DOI: 10.1002/ana.10349
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal asymmetry in language association cortex in autism

Abstract: Autism is a neurodevelopmental disorder affecting cognitive, language, and social functioning. Although language and social communication abnormalities are characteristic, prior structural imaging studies have not examined languagerelated cortex in autistic and control subjects. Subjects included 16 boys with autism (aged 7-11 years), with nonverbal IQ greater than 80, and 15 age-and handedness-matched controls. Magnetic resonance brain images were segmented into gray and white matter; cerebral cortex was parc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
185
4
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(214 citation statements)
references
References 67 publications
21
185
4
4
Order By: Relevance
“…At 200-300ms, problems with change detection and rapid temporal processing are apparent. Hemispheric differences also exist, with some suggestion of right hemisphere abnormalities, perhaps consistent with emerging evidence from structural studies which implicate right hemisphere substrates in ASD (De Fosse et al, 2004;Herbert et al, 2002). That said, atypical left hemispheric responses in mismatch and RTP paradigms are also observed in ASD, reflective of language impairment.…”
Section: Resultssupporting
confidence: 65%
“…At 200-300ms, problems with change detection and rapid temporal processing are apparent. Hemispheric differences also exist, with some suggestion of right hemisphere abnormalities, perhaps consistent with emerging evidence from structural studies which implicate right hemisphere substrates in ASD (De Fosse et al, 2004;Herbert et al, 2002). That said, atypical left hemispheric responses in mismatch and RTP paradigms are also observed in ASD, reflective of language impairment.…”
Section: Resultssupporting
confidence: 65%
“…While this could be related to abnormalities of asymmetry reported in other brain imaging studies of autism (e.g., Herbert et al, 2002), statistical assessment of asymmetry did not show significant group differences.…”
Section: Discussionmentioning
confidence: 47%
“…Head circumference and cortical volume are increased in young children (2-6 years of age) with autism (Piven et al, 1996;Courchesne et al, 2001;Sparks et al, 2002) during the same time that cortical 5-HT synthesis lags behind normal. Moreover, numerous studies show structural alterations in the cerebral cortex of children with autism (Bailey et al, 1998;Casanova et al, 2002;Herbert et al, 2002;Levitt et al, 2003). Such changes in the size and architecture of important cortical processing areas may underlie functional deficits in the development of cortical sound processing (Gage et al, 2003), visuo-motor maps (Mueller et al, 2003) and face recognition Dawson et al, 2002) that are observed in autism.…”
Section: Neonatal Serotonin Depletions As An Animal Model For Autismmentioning
confidence: 99%